Should colorectal cancer screening be considered in elderly persons without previous screening?: A cost-effectiveness analysis - Van Hees, F.; Habbema, D.; Meester, R.; Lansdorp_Vogelaar, Iris; Van Ballegooijen, M.; Zauber, A. (2014)
Background: The U.S. Preventive Services Task Force recommends against routine screening for colorectal cancer (CRC) in adequately screened persons older than 75 years but does not address the appropriateness of screening in elderly persons without previous screening. Objective: To determine at what ages CRC screening should be considered in unscreened elderly persons and to determine which test is indicated at each age. Design: Microsimulation modeling study. Data Sources: Observational and experimental studies. Target Population: Unscreened persons aged 76 to 90 years with no, moderate, and severe comorbid conditions. Time Horizon: Lifetime. Perspective: Societal. Intervention: One-time colonoscopy, sigmoidoscopy, or fecal immunochemical test (FIT) screening. Outcome Measures: Quality-adjusted life-years gained, costs, and costs per quality-adjusted life-year gained. Results of Base-Case Analysis: In unscreened elderly persons with no comorbid conditions, CRC screening was cost-effective up to age 86 years. Screening with colonoscopy was indicated up to age 83 years, sigmoidoscopy was indicated at age 84 years, and FIT was indicated at ages 85 and 86 years. In unscreened persons with moderate comorbid conditions, screening was cost-effective up to age 83 years (colonoscopy indicated up to age 80 years, sigmoidoscopy at age 81 years, and FIT at ages 82 and 83 years). In unscreened persons with severe comorbid conditions, screening was cost-effective up to age 80 years (colonoscopy indicated up to age 77 years, sigmoidoscopy at age 78 years, and FIT at ages 79 and 80 years). Results of Sensitivity Analyses: Results were most sensitive to assuming a lower willingness to pay per quality-adjusted life-year gained. Limitation: Only persons at average risk for CRC were considered. Conclusion: In unscreened elderly persons CRC screening should be considered well beyond age 75 years. A colonoscopy is indicated at most ages. © 2014 American College of Physicians.